2014
DOI: 10.1002/adma.201403237
|View full text |Cite
|
Sign up to set email alerts
|

Blue Liquid Lasers from Solution of CdZnS/ZnS Ternary Alloy Quantum Dots with Quasi‐Continuous Pumping

Abstract: A blue (ca. 440 nm) liquid laser with an ultra-low threshold through which quasi-continuous wave pumping is accessible is achieved by engineering unconventional ternary CdZnS/ZnS alloyed-core/shell QDs. Such an achievement is enabled by exploiting the novel gain media with minimal defects, suppressed Auger recombination, and large gain cross-section in combination with high-quality-factor whispering gallery mode resonators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
175
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 136 publications
(184 citation statements)
references
References 47 publications
6
175
1
2
Order By: Relevance
“…A first strategy consisted of filling the core of an optical fiber with a 30001-p12 I. Suárez Alvarez: Active photonic devices based on colloidal semiconductor nanocrystals and organometallic halide perovskites colloidal solution of CdZnS/ZnS QDs (emission at 440 nm) [72]. Whispering gallery modes of the cover provided the required feedback to demonstrate 5 nm narrow laser lines with a threshold of 14.7 mJ/cm 2 under nanosecond excitation.…”
Section: -P11mentioning
confidence: 99%
“…A first strategy consisted of filling the core of an optical fiber with a 30001-p12 I. Suárez Alvarez: Active photonic devices based on colloidal semiconductor nanocrystals and organometallic halide perovskites colloidal solution of CdZnS/ZnS QDs (emission at 440 nm) [72]. Whispering gallery modes of the cover provided the required feedback to demonstrate 5 nm narrow laser lines with a threshold of 14.7 mJ/cm 2 under nanosecond excitation.…”
Section: -P11mentioning
confidence: 99%
“…Later, this group employed these QDs on distributed feedback gratings to achieve lasing [104,105] with power conversion efficiencies reaching 28% for the red lasers [105]. An interesting study on the lasing of QD solution was reported by Wang et al [106] In this work, blue-emitting CdZnS/ZnS ternary alloyed QDs were synthesized to obtain high-efficiency emitters with suppressed Auger recombination. These QDs were later incorporated into hollow fused silica fibers, in which whispering gallery modes provided the feedback mechanism required for lasing.…”
Section: Lasers Of Colloidal Materialsmentioning
confidence: 99%
“…We can evoke red-light-emitting diodes (LEDs) fabricated using CdSe/ Cd 1-x Zn x S quantum dots (QDs) [21], blue (∼440 nm) liquid laser with an ultra-low threshold achieved by engineering unconventional ternary CdZnS/ZnS alloyed-core/shell QDs [22] and fluorescent CdS QDs utilized for the direct detection of fusion proteins [23]. Furthermore, Cd 1-x Zn x S QDs have become one of the most promising materials in solar cell area [24].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning Cd 1−x Zn x S quantum dots (QDs), their considerable advantage has been demonstrated in both fundamental and applied research [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%